2001
DOI: 10.1007/s004410100395
|View full text |Cite
|
Sign up to set email alerts
|

Calbindin immunoreactivity of enteric neurons in the guinea-pig ileum

Abstract: Previous studies have identified Dogiel type II neurons with cell bodies in the myenteric plexus of guinea-pig ileum to be intrinsic primary afferent neurons. These neurons also have distinctive electrophysiological characteristics (they are AH neurons) and 82-84% are immunoreactive for calbindin. They are the only calbindin-immunoreactive neurons in the plexus. Neurons with analogous shape and electrophysiology are found in submucosal ganglia, but, with antibodies used in previous studies, they lack calbindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
35
0
3

Year Published

2001
2001
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 32 publications
3
35
0
3
Order By: Relevance
“…This value closely agrees with published data (Costa et al, 1996;Li and Furness, 2000;Quinson et al, 2001). Because these are cholinergic neurons (Costa et al, 1996) and we have shown that nearly all cholinergic neurons express CB 1 receptors, it was not surprising to find that over 90% of calbindin-positive neurons were also labelled for CB 1 receptors.…”
Section: Discussionsupporting
confidence: 89%
“…This value closely agrees with published data (Costa et al, 1996;Li and Furness, 2000;Quinson et al, 2001). Because these are cholinergic neurons (Costa et al, 1996) and we have shown that nearly all cholinergic neurons express CB 1 receptors, it was not surprising to find that over 90% of calbindin-positive neurons were also labelled for CB 1 receptors.…”
Section: Discussionsupporting
confidence: 89%
“…It is believed that calbindin is a marker for intrinsic primary afferent neurones in the guinea-pig ileum (Quinson et al 2001). In the guinea-pig ileum, P2X 3 receptors did not to coexpress with calbindin D-28 (Poole et al 2002;Van Nassauw et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Four classes of nerve cell bodies account for almost all neurons in the submucosal ganglia of the guinea-pig ileum (Furness et al 1984;Quinson et al 2001). These are: (1) Dogiel type II neurons, immunoreactive for choline acetyltransferase (ChAT), tachykinins and calbindin (about 10% of nerve cells), (2) neurons immunoreactive for calretinin and ChAT (about 15%), (3) neurons with VIP immunoreactivity (about 45%) and (4) neurons with both NPY and ChAT immunoreactivity (about 30%).…”
Section: Discussionmentioning
confidence: 99%